Monitoring mental health of college students using smartphones - Barnes, Laura (2019)
A better understanding of an individual’s smartphone use can help researchers to improve methods for early detection, evaluation, and intervention of anxiety disorders. For this reason, we present an exploratory study of behavioral markers extracted from smartphone data. We examine fine-grained behaviors before and after smartphone communication events across social anxiety levels. To discover behavioral markers, we model the smartphone as a linear dynamical system with the accelerometer data as output. In a two-week study of 52 college students, we find substantially different behavioral markers prior to and after outgoing phone calls when comparing individuals with high and low social anxiety.